Science communication and its relevance to society - Podgórniak-Krzykacz, Aldona (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
Science, like science communication, is an ambiguous concept. It satisfies people’s intellectual needs, it is oriented towards the common good, and it is the ultimate reference point for public, business, and individual decisions. Its usefulness and novelty result in the use of the scientific work effects and in the diffusion of research in the economy. Scientific research is a driving force for economic and social success.Science communication is a process in which scientists, with the appropriate competences, enter into a purposeful, informed dialogue with society through various media. It is followed by critical analysis and the reorientation of people’s thinking, which influences their opinions, so their choices and decisions are more appropriate. Science communication draws from many disciplines, and it finds itself on their borders. It is both interdisciplinary and transdisciplinary. It is now an arena where many stakeholders compete for attention and advantage, shaping public debate.Nowadays, science communication is gaining importance due to the global trend towards the democratisation of science. In the information age, widespread access to ICT, and the rise of the use of artificial intelligence, reflection, as well as an informed and critical view of the surrounding world, are crucial in the lives of modern people and in countering “scientific exclusion”.Science communication has moved from a one-way communication of scientific facts and information through dialogue with the public and is moving towards full participatory engagement, based on multi-directional communication, co-production, co-creation and comprehensive collaboration.